Multi‐Event Analysis of Plasma and Field Variations in Source of Stable Auroral Red (SAR) Arcs in Inner Magnetosphere During Non‐Storm‐Time Substorms. Issue 4 (26th March 2021) - Inaba, Yudai; Shiokawa, Kazuo; Oyama, Shin‐ichiro; Otsuka, Yuichi; Connors, Martin; Schofield, Ian; Miyoshi, Yoshizumi; Imajo, Shun; Shinbori, Atsuki; Gololobov, Artem Yu; Kazama, Yoichi; Wang, Shiang‐Yu; et al.
Abstract: Stable auroral red (SAR) arcs are optical events with dominant 630.0‐nm emission caused by low‐energy electron heat flux into the topside ionosphere from the inner magnetosphere. SAR arcs are observed at subauroral latitudes and often occur during the recovery phase of magnetic storms and substorms. Past studies concluded that these low‐energy electrons were generated in the spatial overlap region between the outer plasmasphere and ring‐current ions and suggested that Coulomb collisions between plasmaspheric electrons and ring‐current ions are more feasible for the SAR‐arc generation mechanism rather than Landau damping by electromagnetic ion cyclotron waves or kinetic Alfvén waves. This work studies three separate SAR‐arc events with conjunctions, using all‐sky imagers and inner magnetospheric satellites (Arase and Radiation Belt Storm Probes [RBSP]) during non‐storm‐time substorms on December 19, 2012 (event 1), January 17, 2015 (event 2), and November 4, 2019 (event 3). We evaluated for the first time the heat flux via Coulomb collision using full‐energy‐range ion data obtained by the satellites. The electron heat fluxes due to Coulomb collisions reached ∼10 9  eV/cm 2 /s for events 1 and 2, indicating that Coulomb collisions could have caused the SAR arcs. RBSP‐A also observed local enhancements of 7–20‐mHz electromagnetic wave power above the SAR arc in event 2. The heat flux for the freshly detached SAR arc in event 3 reached ∼10 8  eV/cm 2 /s, which is insufficient to have caused the SAR arc. In event 3, local flux enhancement of electrons (<200 eV) and various electromagnetic waves were observed, these are likely to have caused the freshly detached SAR arc. Plain Language Summary: Stable auroral red (SAR) arcs are aurora with an optical red emission from oxygen atoms at latitudes slightly lower than the auroral oval and often occur during storm‐time substorms. The oxygen excitation is caused by low‐energy electrons transferred from the inner magnetosphere to the ionosphere. Past studies concluded that these low‐energy electrons were generated in the spatial overlap region between the plasmaspheric cold electrons and high‐energy ring‐current ions and suggested that Coulomb collisions are more plausible as the generation mechanism of SAR arcs than are electromagnetic waves. In this study, we report three SAR‐arc events observed by all‐sky imagers and inner magnetospheric satellites (Arase and Radiation Belt Storm Probes). We evaluated for the first time the three possible activation mechanisms using the data for full‐energy‐range plasma and electromagnetic wave data obtained by the satellites. As predicted previously, the calculated heat flux could have caused the SAR arcs in two of the events, but there were mixed cases in which electromagnetic waves were observed. When Arase flew above a freshly generated SAR arc, the flux of low‐energy electrons (<200 eV) was enhanced and various electromagnetic waves were observed, which may be responsible for its generation. Key Points: Heat fluxes estimated from Radiation Belt Storm Probes (RBSP) reached the order of 10 9  eV/cm 2 /s, indicating that Coulomb collisions could be the cause of stable auroral red (SAR) arcs The RBSP‐A satellite observed local enhancements of 7–20‐mHz electromagnetic wave power above a SAR arc Arase observed increases of electron fluxes (<200 eV) and various electromagnetic waves above a freshly detached SAR arc